2015
DOI: 10.1080/00325481.2015.1045815
|View full text |Cite
|
Sign up to set email alerts
|

Individual and societal consequences of hypoglycemia: A cross-sectional survey

Abstract: A high proportion of insulin-treated patients experience hypoglycemia resulting in fear of hypoglycemia and changes in self-care behavior that may compromise glycemic control. Many patients with a history of severe hypoglycemia consider underreporting hypoglycemic events through concern over retaining their driving license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
0
33
1
1
Order By: Relevance
“…There may also be reluctance on the part of patients to let their normal diabetes team know about SH events, in case they feel clinical teams will be critical, or that it may effect holding a driving license [6]. Patients may under report SH episodes because of this risk, and people who under report in this way are more likely to have further SH episodes [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There may also be reluctance on the part of patients to let their normal diabetes team know about SH events, in case they feel clinical teams will be critical, or that it may effect holding a driving license [6]. Patients may under report SH episodes because of this risk, and people who under report in this way are more likely to have further SH episodes [6].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients experiencing a SH episode attended by Ambulance Crew in the UK do not have evidence of further contact with primary or secondary care diabetes services [18,27] Many SH patients feel they have had only limited education in hypoglycaemia avoidance and management [1] and the lack of further education and support means patients do not have an opportunity to have an individualised glycaemic target reviewed (29), or access education and advice on hypoglycaemia avoidance [1,2,29 -31]. There may also be reluctance on the part of patients to let their normal diabetes team know about SH events, in case they feel clinical teams will be critical, or that it may effect holding a driving license [6]. Patients may under report SH episodes because of this risk, and people who under report in this way are more likely to have further SH episodes [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A further study in Denmark reported that 23% of drivers with diabetes holding a Group 1 licence and 16% of those holding a Group 2 licence would consider under-reporting their episodes of severe hypoglycaemia. 13 Two or more episodes of severe hypoglycaemia in the last 12 months were reported by 10.4% of participants with a current driving licence, suggesting that underreporting of severe hypoglycaemia was indeed commonplace. In a survey of attitudes to the EU regulations in drivers with insulintreated diabetes in the Czech Republic, many averred that they would conceal exposure to recent severe hypoglycaemia because they feared losing their driving licence.…”
Section: Can We Identify Drivers With Diabetes At Risk Of Road Traffimentioning
confidence: 99%